(untitled) (International Current Pharmaceutical Journal, 2016)
Skin being the primary barrier to infection can be damaged by burn injury. Burn injury may lead to distributive, hypovolemic and cardiogenic shock. A burn victim may experience several extremely mortal complications i.e. local and systemic. When the injury exceeds 25 to 30% total body surface area (TBSA) there will be the chances of generalized edema in non-injured tissues. Fluid resuscitation is very effective method in the management of major burn. According to the expert opinion, the fluid resuscitation should be started in adults with 15% and children with 10% burns. In this review article, it has been concluded that opioids, anticonvulsants, antidepressants, benzodiazepines and ketamine are the most commonly used drugs in the management of burn pain. Silver compound or its salts mainly Silver sulfadiazine is an important remedy in topical treatment. Sepsis is the main cause of death in burn victims. Masood et al., International Current Pharmaceutical Journal, November 2016, 5(12): 103-105 http://www.icpjonline.com/documents/Vol5Issue12/01.pdf